A gold lamella for ‘Blessed’ Abalala - Kotansky, Roy D. (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This article examines a previously unpublished gold lamella of unknown provenance, datable on palaeographical grounds to the 1st century BCE, give-or-take a half century, either side. The tablet preserves three words written in Greek letters that may contain a GrecoPersian formula of protection in the afterlife for its bearer, Abalala, a name of pre-Islamic extraction. The study compares the formula with those on a number of shorter ‘Orphic’ gold lamellae to show that the tiny piece represents a ‘Totenpaß’ for the beneficent dead, rather than a protective charm (phylactery) with the usual voces magicae, although the distinction between magic words and meaningful text is not always clear in such instances.